Investigation of self-confidence, academic achievement, intention to leave school and conflict management styles of nursing students - Yeşilbaş, Hande; Kantek, Filiz; Ozen, Tangul Aytur (My University, 2024)
Objective: This study aimed to investigate the relationship between nursing students' self-confidence, academic achievement, intention to leave school and conflict management styles. Material and Method: This study was a descriptive correlational design with a convenience sample of 573 nursing students. Data were collected using the Rahim Organizational Conflict Inventory II (ROCI II), the Self-confidence Scale and the Personal Information Form. The descriptive statistics, correlation analysis and regression analysis were performed for the data analysis. Results: Integrating style subdimension was found to have the highest score while dominating subdimension had the lowest score. 83.1% of the students did not think of leaving school. The study results suggested a positive correlation between self-confidence and integrating subdimension (r=.408, p=.000), obliging (r=.085, p=.042), dominating (r=.310, p=.000), and compromising (r=.344, p=.000) subdimensions. Conclusion: Nursing students' conflict management styles was related to self-confidence and academic achievement. Intention to leave school was not correlated with conflict management styles. Faculty managers should notice nursing students with low self-confidence and inadequate skills of conflict management and plan specifically designed initiatives for these students.
Keywords: Self-Confidence; Nursing Students; Academic Achievement; Conflict Management Styles; Intention to Leave School